2016
DOI: 10.1177/0271678x15621253
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in neurovascular reactivity after subarachnoid hemorrhage in vivo

Abstract: Subarachnoid hemorrhage causes acute and long-lasting constrictions of pial arterioles. Whether these vessels dilate normally to neuronal activity is of great interest since a mismatch between delivery and consumption of glucose and oxygen may cause additional neuronal damage. Therefore, we investigated neurovascular reactivity of pial and parenchymal arterioles after experimental subarachnoid hemorrhage. C57BL/6 mice were subjected to subarachnoid hemorrhage by filament perforation or sham surgery. Neurovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Recent ex vivo studies investigating intraparenchymal arterioles in rats after SAH reported an inversion of NVC: arterioles constricted rather than dilated in response to neuronal activity 24 to 96 h after SAH. 30 While our previous study investigating neurovascular reactivity showed that NVC is not impaired within the first few hours after SAH, 11 in the current study, we unequivocally demonstrate in vivo and ex vivo a progression in vascular dysfunction, affecting NVC 24 h after SAH. These findings define a therapeutic time window that could lead to an improvement in the outcome of already promising approaches like NO-based strategies, i.e.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Recent ex vivo studies investigating intraparenchymal arterioles in rats after SAH reported an inversion of NVC: arterioles constricted rather than dilated in response to neuronal activity 24 to 96 h after SAH. 30 While our previous study investigating neurovascular reactivity showed that NVC is not impaired within the first few hours after SAH, 11 in the current study, we unequivocally demonstrate in vivo and ex vivo a progression in vascular dysfunction, affecting NVC 24 h after SAH. These findings define a therapeutic time window that could lead to an improvement in the outcome of already promising approaches like NO-based strategies, i.e.…”
Section: Discussionsupporting
confidence: 49%
“…Mice were re-anesthetized 24 h after SAH and the CBF response after NVC was evaluated as previously described. 11,17 Briefly, the left forepaw was stimulated with two subdermal needle electrodes with a diameter of 0.2 mm (Hwato, Suzhou, China) at an intensity of 2 mA for 0.3 ms (Digitimer Ltd, Hertfordshire, England). One stimulation cycle contained 96 stimulations and lasted for 16 s (6 Hz).…”
Section: Forepaw-evoked Nvcmentioning
confidence: 99%
“…In both SAH and CADASIL, dysregulation of brain PA reactivity precedes the onset of neurological deficits. Using well‐established rabbit, rat, and mouse models of SAH, and a transgenic mouse model of CADASIL (TgNotch3 R169C ) in which a human NOTCH3 receptor mutation—the molecular cause of CADASIL—is overexpressed, we have discovered that K V channel activity in PA SMCs is abnormal in both pathological conditions . Although abnormal K V activity could conceivably reflect changes in channel gating properties or recruitment of new K V channel family members, our experimental data demonstrated unchanged τ act , V 0.5 , or k in both disease models.…”
Section: Impact Of Pathological Increases (Cadasil) or Decreases (Sahmentioning
confidence: 79%
“…The vasoconstriction observed after SAH is thought to be caused by elevated potassium concentrations outside ( [39]. Such an inversion of neurovascular coupling has also been demonstrated in vivo [40,41].…”
Section: Pathophysiology Of Subarachnoid Hemorrhagementioning
confidence: 89%